Learning from “Our Relations” Indigenous Peoples of Australia, Canada, New Zealand, and United States: A Review of Culturally Relevant Diabetes and Obesity Interventions for Health - Kurtz, Donna; Janke, Robert; Barry, Julianne; Cloherty, Alexandra; Shahram, Sana Z; Jones, Charlotte A (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2022)
Globally, Indigenous Peoples suffer disproportionately higher rates and complications of diabetes and obesity than non-Indigenous people. Western health interventions combined with culturally appropriate Traditional approaches can reduce incidence, prevalence, and related co-morbidities. This literature review reports effective culturally relevant Traditional and Western diabetes and obesity prevention and management intervention programs for Indigenous populations in Australia, Canada, New Zealand, and the United States. Experiential, immediate, interactive, and low-cost programs, co-developed and delivered by local Indigenous people within the communities they live, are most effective in improving health and wellbeing. Key themes of success of Togetherness, Empowerment, and Local Familiarity inform action for policy and practice changes adaptable for chronic disease prevention, treatment, and self-management programs for Indigenous Peoples globally.